Use of Organic Selenium Supplements in Soybean Meal-Based Diets for Juvenile Yellowtail Kingfish (Seriola lalandi) - Ilham; Fotedar, Ravi; Suyasa, I. (Ommega Publishers, 2016)
Sustainable aquaculture, from both ecological and economic perspectives, demands a substantial reduction of the amount of fishmeal used in aqua feed. Instead, plant-derived protein feed stuff, which provide a nutritious diet offer a promising alternative for inclusion in aqua feed. In this study, the effects of organic selenium supplementation in low and high soybean meal-based practical diets for yellowtail kingfish (Seriola lalandi) were evaluated over a 60-day feeding experiment. The juvenile yellowtail kingfish (initial weight 5.02 ± 0.04 g fish-1) were fed five iso-nitrogenous and iso-caloric diets containing 49% crude protein and 22 MJ kg-1 gross energy. The control diet(C) includes 46% fishmeal, whereas the other diets used soybean meal to replace 25% and 75% of the fishmeal protein, both without and with organic selenium supplementation (SBM25, SBM25+Se, SBM75, and SBM75+Se). Fish were fed ad libitum two times a day at 09:00 and 15:00 hours. No differences were observed in feed intake among dietary treatment groups (P > 0.05). Organic selenium-supplemented diets improved final weight; however, final weight was significantly reduced when fish were fed high soybean meal diets (P < 0.05). Organic selenium supplementation had a significant effect on specific growth rate at low soybean meal diets, but did not affect specific growth rate when fish were fed high soybean meal diets. Selenium accumulation in fish fillet was strongly correlated with selenium concentration in the diets. While fish fed the SBM25+Se diets had significantly higher glutathione peroxidase activity than those fed other diets, the lowest glutathione peroxidase activity was found in fish fed SBM75 diets. Histologically, selenium-deficient diets induced myopathy and alterations in tissue structure were most prevalent in fish fed the SBM75 diet. The findings of this study indicate that, with Se supplementation, soybean meal could supply 25% of the protein in yellowtail kingfish diets.